Six Sigma Implementation and Integration within Project Management Framework in Engineering, Procurement, and Construction Projects - A Case Study in a Southeast Asian Engineering, Procurement, and Construction Company - THAMRIN, DIVIEZETHA ASTRELLA FLORINDA (My University, 2017)
This thesis was carried out in a Southeast Asian EPC company based in Indonesia, as a mandatory requirement for Master’s degree in Chalmers University of Technology. The thesis was conducted from January 2017 until June 2017 by a student from M.Sc. International Project Management course. In 2015, a survey from PMI found that there were only 64% of projects which met their goals. The projects included ones conducted in Engineering, Procurement, and Construction (EPC) companies. The bigger projects were more likely to encounter bigger problems, which results in poor performance which ultimately affected the quality of projects. As a result, more companies are seeking quality improvement methodologies like Six Sigma and merging it within the project management framework. This provided an excellent opportunity for a thesis study, which was to investigate how an EPC company works with quality management and what leads to successful integration of Six Sigma methodology in EPC project management framework. The aim of the study was to identify the success factors, benefits and constraints of Six Sigma implementation in project management, so as to successfully merge it to the knowledge areas within project management framework. A qualitative approach was used to perform this study. The study included state of the art literature review and a case study. Data for the study was gathered through semi-structured interviews with employees from the case company. In addition to the interviews, data was also obtained from internal documentation. There were three main theoretical frameworks used in this study: the Six Sigma DMAIC Methodology, Six Sigma Project Management, and Six Sigma Implementation Success Factors. The foundation for the findings and discussions in this study are generated through these theories. The study disclosed that quality has not been the main concern in EPC projects. Albeit there has been sets of standardisation to achieve a certain level of quality, the EPC company has not really felt the necessity in enforcing it rigorously. Also, there are several challenges connected to the project management practices such as poor communication, inefficient project processes, disintegrated and complicated workflows, and limited access to project information. After challenges were identified, the existing framework within Six Sigma DMAIC was updated based upon the expected success factors for ideal vision of project lifecycle from the empirical findings, to accommodate solutions for the identified challenges. This thesis resulted in providing an updated framework for Six Sigma project management in EPC context. The identification of success factors for Six Sigma implementation in EPC projects and its benefits are seemed to outweigh the constraints. It is recommended for future research to further investigate the real cause of the low awareness of quality management in EPC projects, formulate a better standardised workflow for EPC industry, and investigate the suitable type of organisation structure for EPC projects.
Keywords: Samhällsbyggnadsteknik; Civil Engineering